Electrodialytic recovery of phosphorus and organic contaminants removal from sewage sludge - Almeida, Joana Saraiva Rocha de (2016)
Phosphorus is a macronutrient essential to life which comes from phosphate rock, a non-renewable resource. Sewage sludge from wastewater treatment plants (WWTP) is a secondary resource rich in phosphorus that can be valorized. However, organic compounds are detected in sewage sludge, due to its non-polar and hydrophobic character, being considered an environmental risk. The present dissertation aims to study the efficiency of the electrodialytic process (ED) when applied to sewage sludge aiming phosphorus recovery and organic contaminants removal. Four organic compounds were analyzed: 17α-ethynylestradiol (EE2), bisphenol A (BPA), caffeine (Caf) and oxybenzone (MBPh). The experiments took place in an ED cell with two compartments and an anion exchange membrane, with the sludge in the cathode compartment. The experiments were carried out for three days with spiked sewage sludge (six assays). One control experiment was done without current, three experiments were carried out applying a constant current of 50, 75, and 100 mA and two experiments were carried out applying sequential currents: 50 mA, 75 mA and 100 mA and the opposite (100-75-50 mA). A qualitative and quantitative analysis of microorganisms existing in the samples was also done. At the end, the pH increased in the sewage sludge favoring phosphorus recovery. In terms of phosphorus, the highest recovery was achieved in the experiment run with 100 mA, where 70.3±2.0% of total phosphorus was recovered in the electrolyte. Generally, compounds degradation was favored by the current. Caf and MBPh achieved degradation percentages of 96.2±0.2% and 84.8±1.3%, respectively, in 100 mA assay. EE2 (83.1±1.7%) and BPA (91.8±4.6%) degradations were favored by 50 mA current. A total of 35 taxa from four different groups were identified, totalizing between 81,600-273,000 individuals per gram of initial sludges. After ED, microbial community population decreased between 47-98%. Arcella gibbosa represented 61% of the total observed organisms and revealed to be more tolerant to medium changes.